Optimalisasi Peran Dasawisma dalam Pencegahan Penyakit Tidak Menular melalui Edukasi Kesehatan dan Skrining Komunitas di Dusun Candidukuh: Strengthening the Role of Dasawisma in Non-Communicable Disease Prevention through Health Education and Community-Based Screening in Candidukuh Hamlet - Sri Sahayati; Merita Eka Rahmuniyati; Natalya Anastasya Valentin; Zahro Khoirunnisa (Poltekkes Kemenkes Yogyakarta, 2025)
Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, hypercholesterolemia, and hyperuricemia remain major public health problems that continue to increase and negatively affect family quality of life. Limited public awareness regarding early detection and insufficient knowledge of healthy lifestyles are major challenges among Dasawisma women’s groups as key managers of family health. This community service program aimed to improve the knowledge and health awareness of Dasawisma women regarding NCD prevention through health education and basic health screening. The activity was conducted on August 18, 2024, in Candidukuh Hamlet involving 40 Dasawisma women ranging from adulthood to older age. The intervention employed a participatory health education approach through lectures, interactive discussions, pretest–posttest assessments, and health screening including blood pressure, blood glucose, cholesterol, and uric acid examinations. The results demonstrated an improvement in participants’ understanding of healthy lifestyles, early detection of NCDs, and management of health risk factors. Screening results showed that 55% of participants had normal blood pressure, while 45% were identified with hypertension, and several participants had elevated levels of blood glucose, cholesterol, and uric acid. Participants showed high enthusiasm throughout the program and began to understand the importance of regular health check-ups as a preventive effort. This program was effective in improving community health literacy and strengthening the role of Dasawisma as a community-based health empowerment forum in supporting sustainable promotive and preventive efforts for NCD control.